Laryngeal Imaging: Anatomy and Pathology - Solanki, Rajendra; Prajapati, Pooja (Indographics, 2022)
Imaging plays an important role in diagnostic evaluation of laryngeal lesions. The real value of imaging comes when there is a need to decide the feasibility of speech conservation therapy. Cross-sectional imaging allows excellent depiction of the intricate anatomy of the larynx and the characteristic patterns of tumor extension as well as the status of cervical nodal disease. Imaging studies also help in the post-therapeutic follow-up of patients with laryngeal cancers. In this article, we review the currently used laryngeal imaging techniques and protocols, the key anatomic structures relevant to tumor spread and the characteristic patterns of submucosal extension and invasion of laryngeal cancer. The role of CT and MRI in the evaluation of patients with laryngeal SCC and the impact of imaging findings, staging and surgical aspects is also discussed.
Keywords: larynx; neck; cartilage